1999
DOI: 10.4141/p97-017
|View full text |Cite
|
Sign up to set email alerts
|

Shearing force of alfalfa stems: effects of cultivar and shearing site

Abstract: Smith, J. G. 1999. Shearing force of alfalfa stems: effects of cultivar and shearing site. Can. J. Plant Sci. 79: 49-55. A 3-yr study was conducted to investigate the effect of shearing position on shearing force characteristics in alfalfa (Medicago sativa L.) stems and to evaluate the relationship between cell wall (CW) chemical constituents and stem shearing force. Stems from plots of 24 alfalfa cultivars were harvested from the second, third and fourth production years. Each stem was divided into three 16-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…All stems sampled for this study began growth at approximately the same time and therefore added a similar number of internodes to their tips over the 15-wk regrowth period. Shear force was also found to be greater in lower than upper stem segments of alfalfa and was significantly correlated with lignin concentration (Ames et al, 1995;Iwaasa et al, 1995Iwaasa et al, , 1999. This progression of growth and lignification of a basal stem internode has already been assessed for alfalfa (Engels and , which forms a dark blueblack precipitate with tannins.…”
Section: Discussion Stem Growth and Developmentmentioning
confidence: 74%
See 2 more Smart Citations
“…All stems sampled for this study began growth at approximately the same time and therefore added a similar number of internodes to their tips over the 15-wk regrowth period. Shear force was also found to be greater in lower than upper stem segments of alfalfa and was significantly correlated with lignin concentration (Ames et al, 1995;Iwaasa et al, 1995Iwaasa et al, , 1999. This progression of growth and lignification of a basal stem internode has already been assessed for alfalfa (Engels and , which forms a dark blueblack precipitate with tannins.…”
Section: Discussion Stem Growth and Developmentmentioning
confidence: 74%
“…They reported a decrease in both internode diameter and secondary xylem thickness that progressed linearly from the base to the tip of stems and found that internodes located close to the base of the stem, such as Internode 6, had more lignified xylem tissue than internodes closer to the stem tip. Shear force was also found to be greater in lower than upper stem segments of alfalfa and was significantly correlated with lignin concentration (Ames et al, 1995;Iwaasa et al, 1995Iwaasa et al, , 1999. The elevated level of shear strength that prevented sheep from harvesting mature BFT stems, as observed by Douglas et al (1999), was likely due to thickening and lignification of the xylary ring of BFT that had progressed to stem internodes above a desirable grazing height.…”
Section: Stem Growth and Developmentmentioning
confidence: 86%
See 1 more Smart Citation